National poverty alleviation strategy and policy regulation exemption: A quasi-natural experiment based on the green credit guidelines - Wang, Wei; Ma, Jingjuan; Li, Sihai; Liu, Lin (Frontiers in Environmental Science, 2022)
This paper evaluates the real effects of the environmental policy at the firm level. Using the promulgation of the "Green Credit Guidelines" and national poverty alleviation strategy as a quasi-natural experiment, we find that:(1) the Guidelines significantly inhibit the scale and maturity of debt financing for polluting companies; (2) the participation of enterprises in poverty alleviation efforts can effectively offset the restraining influence of the Guidelines. Our results are robust for parallel trend assumption and propensity score matching estimation. Futher, we find that state-owned enterprises have decreased more significantly. These results indicate that the national poverty alleviation strategy could play a role in debt financing for polluting companies. Thus providing timely implications for regulators concerned with environmental protection.